Peran Politik Perempuan Pondok Pesantren Ihyaul Ulum Dukun Gresik - Hubet, Abdulla (al-Daulah: Jurnal Hukum dan Perundangan Islam, 2013)
Abstract: One of the factors that encourages women in Ihyaul-Ulum Islamic boarding school in politics is their willingness to participate in the development process, especially in regions. They view that politics is a part of the broadcasting media of the Islamic propaganda. The women?s involvement of Ihyaul-Ulum Islamic boarding school in politics is not merely passive but active. It is either for supporting the ruling party or a certain administrator to delegate one of them to become a candidate in a certain position. The more elected women of the Islamic boarding school show that the political position of women is culturally very significant. They have proved to be a board member of the country, an achievement that deserves to be appreciated. In Islam, women occupy an important position as men do. Islam came with the principle of equality among all humans. The only standard is their capability in performing their duties as a legislator and as a leader.Keywords: Politics of women, Islamic boarding school, Gresik